(untitled) (Revista de Ciências Agroveterinárias, 2018)
Different sources and nitrogen management (N) may increase the availability, absorption, and assimilation of this nutrient by plants, favoring the N accumulation in grains. However, little is known about the influence of these factors on the physiological quality of wheat seeds (Triticum aestivum L.). In this context, the aim of this study was to evaluate the response of different sources and nitrogen fertilization, applied in cover, on the physiological quality of the wheat seeds. The experiment was conducted in a completely randomized block design in a split-design treatment plot with three cultivars of wheat (TBIO Mestre, TBIO Iguaçu and Quartzo), three sources of nitrogen (urea, ammonium nitrate, and liquid urea), applied using five methods: (I: tilling; II: tilling and booting; III: tilling and flowering; IV: booting and flowering and V: tilling, booting and flowering). The nitrogen partitioning between booting and flowering stages results in higher physiological seed quality, since it increases the percentage of germination by 4% and positively influences the germination count, shoot length, and seedling dry mass. The sources of nitrogen ammonia nitrate and the urea liquid source are equated with urea in relation to the effect on the physiological quality of the seeds, being interesting alternatives to reduce the production cost. The TBIO Mestre and Quartzo cultivars showed seeds with higher physiological quality, due to the greater length of radicle and percentage of germination.